Blending of high VFA latex concentrate with low VFA latex concentrate - Sarathkumara P H; Chandima Rohanadeepa V; Warnajith Prasad A K D (Journal of Rubber Research, 2012)
Low ammonia (LA) centrifuged latex of higher volatile fatty acid (VFA) values was blended with that of lower values at different blend ratios. The most important latex characteristics of these blends, namely VFA number, KOH number and MST were tested over a period of time at regular intervals. It was found that centrifuged latex with different VFA values could be blended to obtain a predetermined intermediate VFA value in the final blend. VFA number in the blends as well as in the two unblended latex samples increased gradually after an induction period of 40-50 days. The rate of increase of VFA number was more pronounced in the blends containing higher proportions of high VFA centrifuged latex. A formula was proposed to estimate the VFA number of the final latex blend using the VFA numbers of the initial components of the latex blend. The same formula could be used to estimate the quantity of latex from each latex component to be blended to obtain a targeted VFA value in the final latex blend. After an initial high rate of increase of KOH number in the blends prepared from fresh latex, the rate of increase reduced drastically to almost zero with the increase of maturity. The development of mechanical stability time (MST) of the blends over time was observed to be at par with the development of KOH number barring few exceptions.
Source Year: 2012
Keywords: Blends; Centrifugation; Latices; Proteins